(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The purpose of this study is to evaluate the functional outcomes of arthroscopic treatment for traumatic hip dislocation. Subjects and methods: A retrospective case series was conducted on four patients who suffered from traumatic hip dislocations. All patients initially underwent closed reduction, followed by arthroscopic treatment for intra-articular pathology, between March 2020 and February 2025 at the Lower Limb Department of the Hospital for Traumatology and Orthopedic Ho Chi Minh city. Each patient was followed for at least 2 years postoperatively. Functional outcomes were assessed using the HHS. Results: All patients experienced posterior hip dislocations due to motor vehicle accidents. Intra-articular findings included loose bodies, labral tears, and chondral lesions in 100% of cases. All patients achieved excellent outcomes based on the HHS, with no severe complications. Conclusion: Hip arthroscopy appears to be a safe, effective, and minimally invasive treatment option for managing intra-articular pathologies secondary to traumatic hip dislocation.